THE APPLICATION OF UNIFIED THEORY OF ACCEPTANCE AND USE OF TECHNOLOGY IN MUSICAL METAVERSE - Carlence Maurlen; Henry Susanto Pranoto (Kesatuan Press, 2023)
This research study observes the musical Metaverse and applies the theories of UTAUT (Unified Theory of Acceptance and Use of Technology) and IDT (Innovation Diffusion Theory). It aims to examine the acceptance of the musical Metaverse toward the behavior intention to use (BI), which is influenced by performance expectancy (PE), effort expectancy (EE), social influence (SI), and facilitating conditions (FC), moderated by personal innovativeness (PI). The Google form data was collected from 250 Ciputra University students who familiarized themselves with the musical Metaverse, and the data was later processed using SmartPLS 4. The results showed that PE has a significant effect on BI, EE has no significant effect on BI, and SI has no significant effect on BI. FC has a significant effect on BI; PI has not been able to strengthen other factors to have the intention to use the musical Metaverse. Thus, performance expectancy and facilitating conditions influence the intention to use the musical Metaverse. Meanwhile, personal innovativeness cannot significantly moderate the relationship between PE, EE, SI, and FC